2022
DOI: 10.1111/cod.14034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hand hygiene strategies on skin barrier function during COVID‐19 pandemic: A randomized clinical trial

Abstract: Introduction Coronavirus disease 2019 (COVID‐19) has increased the frequency of handwashing. There is scarce evidence regarding the impact of different hand hygiene procedures on skin barrier function in clinical practice. Objective To compare the impact on skin barrier function of different hand hygiene measures in healthcare workers in daily practice. Methods A randomized controlled clinical trial was conducted. Participants were randomized to sanitize their hands with water and soap, alcohol‐based hand sani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For example, the prevention of irritant contact dermatitis is possible by incorporating alcohol-based hand sanitisers with emollients into the hygiene practices as an alternative to hand washing with water and soap. 5,9,[26][27][28] Furthermore, moisturisers should be used regularly after use of soap and water as a preventive measure to hand dermatitis. 9,27,29 Although skin protection programmes and guidelines for the prevention of HE have been in place for over a decade, 2 moisturisers are frequently used as a therapeutic rather than as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the prevention of irritant contact dermatitis is possible by incorporating alcohol-based hand sanitisers with emollients into the hygiene practices as an alternative to hand washing with water and soap. 5,9,[26][27][28] Furthermore, moisturisers should be used regularly after use of soap and water as a preventive measure to hand dermatitis. 9,27,29 Although skin protection programmes and guidelines for the prevention of HE have been in place for over a decade, 2 moisturisers are frequently used as a therapeutic rather than as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…The strain from hand hygiene practices and wet work can be prevented in different ways. For example, the prevention of irritant contact dermatitis is possible by incorporating alcohol‐based hand sanitisers with emollients into the hygiene practices as an alternative to hand washing with water and soap 5,9,26–28 . Furthermore, moisturisers should be used regularly after use of soap and water as a preventive measure to hand dermatitis 9,27,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the pandemic, an increase in the usage of several hand hygiene products, such as soaps, alcoholbased hand sanitizers (ABHS), and disinfectant wipes, was noted (Montero-Vilchez et al, 2022). Zhang et al (2021) reported that Chinese university students washed their hands an average of 5.76 times per day during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For prevention, rinsing of hands with warm water, the use of moisturizers or hand creams can replenish the moisture and lipids on the skin surface, restoring the skin barrier ( 79 ). While ABHS can also dissolve natural lipids in the epidermis, studies have found that ABHS are less damaging to the epidermal barrier compared to soap ( 96 ). Therefore, individuals who are not allergic to alcohol are advised to choose ABHS instead of soap.…”
Section: Contact Dermatitis Caused By Disinfectant Products During Th...mentioning
confidence: 99%